2013
DOI: 10.1371/journal.pone.0075565
|View full text |Cite
|
Sign up to set email alerts
|

Association of Multiple Sclerosis Susceptibility Variants and Early Attack Location in the CNS

Abstract: ObjectiveThe anatomic location of subsequent relapses in early multiple sclerosis (MS) appears to be predicted by the first attack location. We sought to determine if genetic polymorphisms associated with MS susceptibility are associated with attack location.Methods17 genome-wide association study-identified MS susceptibility polymorphisms were genotyped in 503 white, non-Hispanic patients seen within a year of MS onset. Their association with the CNS location of the first two MS attacks was assessed in multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Though overall susceptibility genes do not appear to have large effects on phenotype, there is some evidence that HLA and non‐HLA genetic risk factors may alter relapse rates, although overall findings are mixed and weak. Some susceptibility polymorphisms have been associated with attack or MRI lesion location and severity . The strongest genetic factor ( HLA‐DRB1*15:01 ) has been associated with earlier age of onset and possibly with greater deep gray matter atrophy .…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 97%
“…Though overall susceptibility genes do not appear to have large effects on phenotype, there is some evidence that HLA and non‐HLA genetic risk factors may alter relapse rates, although overall findings are mixed and weak. Some susceptibility polymorphisms have been associated with attack or MRI lesion location and severity . The strongest genetic factor ( HLA‐DRB1*15:01 ) has been associated with earlier age of onset and possibly with greater deep gray matter atrophy .…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 97%
“…In fact, studies showed that areas of demyelination are commonly localised within previously remyelinated regions [109,110] . This inherent predisposition is likely to be determined by numerous polygenic factors, including genetic factors, such as some of the MS susceptibility factors [111] , several genes involved in the regulation of immune cell function, myelin and neural growth [112] , and genetically correlated CD4 T-cell immunoreactivity [113] .…”
Section: Relapse Phenotypementioning
confidence: 99%
“…rs17810546 locates in a ~70-kb LD block, which is immediately 5′ of IL12A. Similar with the locus RGS1, IL12A has been reported with risk of MS and T1D, confirming the shared genetic factors among different autoimmune diseases [ 22 , 25 ]. In addition, a meta-analysis by Kappen et al [ 26 ] identified the genome wide significance association between IL12A rs17810546 and Behcet’s disease, which was also regarded as a Th1 mediated autoimmune disease.…”
Section: Discussionmentioning
confidence: 64%